2008
DOI: 10.1007/s10709-008-9340-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity and relationships among Cymbidium goeringii cultivars based on inter-simple sequence repeat (ISSR) markers

Abstract: Spring orchid (Cymbidium goeringii) is a popular flowering plant species. There have been few molecular studies of the genetic diversity and conservation genetics on this species. An assessment of the level of genetic diversity in cultivated spring orchid would facilitate development of the future germplasm conservation for cultivar improvement. In the present study, DNA markers of intersimple sequence repeats (ISSR) were identified and the ISSR fingerprinting technique was used to evaluate genetic diversity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 25 publications
2
40
0
4
Order By: Relevance
“…In addition to using SSRs to investigate the highly variable polymorphism of microsatellite loci, ISSR markers are employed. Although ISSR is less informative than SSR by virtue of the dominant nature of ISSR markers, ISSR is still a reliable, cost effective approach that is widely used in plant studies [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to using SSRs to investigate the highly variable polymorphism of microsatellite loci, ISSR markers are employed. Although ISSR is less informative than SSR by virtue of the dominant nature of ISSR markers, ISSR is still a reliable, cost effective approach that is widely used in plant studies [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In Cymbidium goeringii, 25 ISSR primers produced a total of 210 polymorphic fragments, with a mean number of 8.4 fragments per primer (Wang et al, 2009). In Cattleya labiata, a mean number of 12.6 polymorphic fragments per ISSR primer was obtained (151 fragments produced by 12 primers), whereas 11 fragments per primer were obtained using RAPD markers in the same species.…”
Section: Discussionmentioning
confidence: 99%
“…In cultivars from China, only 12 ISSR markers were used, and 342 fragments from 40 bromeliad accessions were obtained (Zhang et al, 2012). In other ornamental families, Wang et al (2009) used 25 ISSR primers to analyze the molecular diversity of 50 cultivars of Cymbidium goeringii and produced 224 fragments (94% polymorphic). Niknejad et al (2009) examined the molecular traits and phylogenetic relationships among orchid species of the Phalaenopsis genus using 10 RAPD markers, producing a total of 414 polymorphic fragments and an average of 41.4 fragments per primer; our study showed lower value, with an average of 17 fragments per primer.…”
Section: Discussionmentioning
confidence: 99%